Lateral femoral condyle cartilage lesions in chronic posterior lateral meniscus root tears: A report of seven cases - Alberto Grassi; Emanuele Altovino; Luca Ambrosini; Claudio Rossi; Luca Andriolo; Giuseppe Filardo; Stefano Zaffagnini (Journal of Experimental Orthopaedics)
Abstract This study aims to investigate the association between chronic lateral meniscus posterior root tears (LMPRTs) and chondral or osteochondral lesions of the lateral femoral condyle (LFC), particularly in cases involving prior anterior cruciate ligament (ACL) injuries. Given the challenges in diagnosing LMPRTs and the biomechanical significance of the lateral meniscus, this research highlights the potential long‐term impact of untreated root tears. A prospective analysis was conducted on seven patients with chronic LMPRTs and suspected LFC lesions, identified through clinical symptoms, history of ACL injuries and magnetic resonance imaging (MRI) findings. The presence of LMPRTs was confirmed via arthroscopy, and the lesions were classified using the LaPrade Classification. The patients underwent various surgical interventions, including ACL reconstruction with lateral tenodesis and meniscus repair. All seven cases demonstrated a significant association between chronic LMPRTs and chondral/osteochondral lesions of the LFC. The lesions were consistently located in the posterolateral compartment, with MRI indicating subchondral bone oedema and cartilage thinning. Surgical findings confirmed Type II posterior root tears in all patients, with subsequent repair. The study suggests that chronic LMPRTs, especially in the context of ACL injuries, may contribute to the development of chondral or osteochondral lesions in the LFC. This association underscores the importance of early diagnosis and treatment of meniscus root tears to prevent long‐term joint degeneration. Increased awareness and improved diagnostic techniques are essential for better clinical outcomes. Level of Evidence: Level IV, case series.